2017
DOI: 10.1038/s41467-017-00539-y
|View full text |Cite
|
Sign up to set email alerts
|

The Gcn4 transcription factor reduces protein synthesis capacity and extends yeast lifespan

Abstract: In Saccharomyces cerevisiae, deletion of large ribosomal subunit protein-encoding genes increases the replicative lifespan in a Gcn4-dependent manner. However, how Gcn4, a key transcriptional activator of amino acid biosynthesis genes, increases lifespan, is unknown. Here we show that Gcn4 acts as a repressor of protein synthesis. By analyzing the messenger RNA and protein abundance, ribosome occupancy and protein synthesis rate in various yeast strains, we demonstrate that Gcn4 is sufficient to reduce protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
91
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 75 publications
12
91
2
Order By: Relevance
“…Here, there is a somewhat contradictory observation, as follows. Several earlier studies have reported, repression of ribosomal gene by the elevated Gcn4 level in cells (Bose et al, 2012;Joo et al, 2010;Mittal et al, 2017). In contrast, here, despite high Gcn4 levels in cells, methionine strongly induces ribosomal and translation related genes.…”
Section: Gcn4 Regulates the Anabolic Component Of The Methionine--depcontrasting
confidence: 67%
See 2 more Smart Citations
“…Here, there is a somewhat contradictory observation, as follows. Several earlier studies have reported, repression of ribosomal gene by the elevated Gcn4 level in cells (Bose et al, 2012;Joo et al, 2010;Mittal et al, 2017). In contrast, here, despite high Gcn4 levels in cells, methionine strongly induces ribosomal and translation related genes.…”
Section: Gcn4 Regulates the Anabolic Component Of The Methionine--depcontrasting
confidence: 67%
“…Gcn4 is a transcriptional master--regulator, conventionally studied in the context of starvation and other stress conditions, as part of the integrated stress response (Hinnebusch, 2005;Hinnebusch and Natarajan, 2002;Mascarenhas et al, 2008;Natarajan et al, 2001;Pakos--Zebrucka et al, 2016). Therefore, nearly all existing studies of Gcn4 have used pharmacological inhibitors of amino acid biosynthesis, such as 3--amino triazole (3--AT) or sulfo meturon (SM) to induce Gcn4 (Akhter and Rosonina, 2016;Albrecht et al, 1998;Mittal et al, 2017;Natarajan et al, 2001;Rawal et al, 2018). Indeed, our current understanding of Gcn4 function comes primarily from contexts of nutrient--stress and starvation conditions.…”
Section: Gcn4 Regulates the Anabolic Component Of The Methionine--depmentioning
confidence: 99%
See 1 more Smart Citation
“…Some are listed below: (i) GH-deficient mouse models have shown improved proteostasis with reduced protein as well as DNA synthesis with sex-and tissue-specific differences (237,238). Most recent ageing research in yeast (239,240) and C. elegans (241) are provocative towards inquiring with the GHRKO model into the status of transcription factors like Gcn4 or Atf4 and proteostasis status. (ii) Bartke and colleagues, have dealt intensively into various conditions of GH deficit and ageing (198,242) and recently reported that a short (6 weeks) phase of early exposure to GH (starting at 2 weeks age) reduced lifespan and cellular stress resistance in Ames dwarf mice (243).…”
Section: Future Directions Of Lifespan Studies On Ghrko Micementioning
confidence: 99%
“…Construction of GRNs based on the transcription factors in these pathways has had mixed success; the high redundancy of the NCR pathway has proven challenging to deconvolute (Milias-Argeitis et al, 2016) . The GAAC pathway is more straightforward, although separating direct and indirect regulation remains difficult, even with high-quality experimental data (Mittal et al, 2017) . As a result, a comprehensive GRN for nitrogen metabolism has remained elusive, despite successes in identifying genes that respond to changes in environmental nitrogen (Airoldi et al, 2016) and identification of post-transcriptional control mechanisms that underlie these changes (Miller et al, 2018) .…”
Section: Introductionmentioning
confidence: 99%